1991
DOI: 10.1093/brain/114.5.2203
|View full text |Cite
|
Sign up to set email alerts
|

The Neurology of Obsessional Slowness

Abstract: Seventeen of 59 patients admitted to hospital for treatment of Obsessive-Compulsive Disorder (OCD) were found to have significant slowness, mainly due to difficulty in initiating goal-directed action and suppressing intrusive and perseverative behaviour. In this subgroup subtle neurological abnormalities were found more frequently than in healthy controls and included loss of motor fluency, hesitancy of initiation of limb movements, speech and gait abnormalities, cogwheel rigidity, complex repetitive movements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
1
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(81 citation statements)
references
References 0 publications
2
76
1
2
Order By: Relevance
“…In contrast, the selective activation of coupling within limbic circuits that occurs upon withdrawal from repeated amphetamine administration (Onn and Grace 2000) may also lead to a type of "cognitive" stereotypy, such as the perseverative drug-seeking behavior demonstrated as a consequence of drug abuse. Within this context, the present findings on the actions of gap junction inactivators may have relevance for diseases such as obsessive-compulsive disorder, drug abuse, and schizophrenia, or other disorders that are associated with disruption of cognitive and/or motor sequencing (Berger et al 1989;Cools et al 2001;Hymas et al 1991;Ridley 1994;Sullivan et al 2001).…”
Section: The Role Of Gap Junctions and Dopamine In Signal Flow Acrossmentioning
confidence: 90%
“…In contrast, the selective activation of coupling within limbic circuits that occurs upon withdrawal from repeated amphetamine administration (Onn and Grace 2000) may also lead to a type of "cognitive" stereotypy, such as the perseverative drug-seeking behavior demonstrated as a consequence of drug abuse. Within this context, the present findings on the actions of gap junction inactivators may have relevance for diseases such as obsessive-compulsive disorder, drug abuse, and schizophrenia, or other disorders that are associated with disruption of cognitive and/or motor sequencing (Berger et al 1989;Cools et al 2001;Hymas et al 1991;Ridley 1994;Sullivan et al 2001).…”
Section: The Role Of Gap Junctions and Dopamine In Signal Flow Acrossmentioning
confidence: 90%
“…Another source of heterogeneity is the use of different standardized instruments to measure NSS, with some studies employing clinical examinations rather than standardized instruments (e.g. Hymas et al 1991 ;Caramelli et al 1996), thus making comparisons difficult.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies have detected impairments of nonverbal memory in patients with OCD, which have been attributed to failures in the employment of appropriate organizational strategies [Kim et al, 2002;Savage et al, 1999;Shin et al, 2004], whereas other studies have reported detecting set-shifting deficits [Aycicegi et al, 2003;Hymas et al, 1991;Veale et al, 1996], and decisionmaking [Cavedini et al, 2002] and response inhibition [Aycicegi et al, 2003;Bannon et al, 2002], all of which are known to be dependent on the frontal cortex [Chamberlain et al, 2005].…”
Section: Introductionmentioning
confidence: 99%